Предмет: Алгебра,
автор: evglevan
Решите уравнение: (x+6)(x-1)-(x+3)(x-4)=5x
Ответы
Автор ответа:
0
(x+6)умножить на(х-1)(х+3)умножить(х-4)=5
х в квадрате -х+6х-6-(х в квадрате-4х+3х-12)=5
х в квадрате -х+6х-6-(х в квадрате-х-12)=5
х в квадрате -х=6х-6-х в квадрате +х+12=5х
6х-5х=-6
х=-6
х в квадрате -х+6х-6-(х в квадрате-4х+3х-12)=5
х в квадрате -х+6х-6-(х в квадрате-х-12)=5
х в квадрате -х=6х-6-х в квадрате +х+12=5х
6х-5х=-6
х=-6
Похожие вопросы
Предмет: Физика,
автор: lomi20
Предмет: География,
автор: boduawertaf
Предмет: Английский язык,
автор: Аноним
Предмет: Математика,
автор: metiska270688
Предмет: География,
автор: aziza261